Real‐world experience of 12‐week direct‐acting antiviral regimen of glecaprevir and pibrentasvir in patients with chronic hepatitis C virus infection. Issue 5 (19th November 2019) - Toyoda, Hidenori; Atsukawa, Masanori; Watanabe, Tsunamasa; Nakamuta, Makoto; Uojima, Haruki; Nozaki, Akito; Takaguchi, Koichi; Fujioka, Shinichi; Iio, Etsuko; Shima, Toshihide; Akahane, Takehiro; Fukunishi, Shinya; et al.
Abstract: Background: In clinical trials, a pangenotype direct‐acting antiviral (DAA) regimen consisting of glecaprevir (GLE) and pibrentasvir (PIB) exhibited high virologic efficacy and tolerability in patients with hepatitis C virus (HCV) infection. This study sought to confirm these findings in real‐world settings, focusing on patients with cirrhosis, history of DAA failure, or HCV genotype 3 who were treated with a 12‐week regimen in a large multicenter study from Japan. Methods: In a nationwide multicenter prospective cohort study, we analyzed background characteristics, tolerability, and treatment outcome of patients who underwent a 12‐week GLE/PIB regimen. Results: Of 1190 patients, 509 (42.8%) underwent the 12‐week regimen, and the remaining patients underwent an 8‐week regimen. The rate of sustained virologic response (SVR) of patients treated with the 12‐week regimen was 99.0%, comparable with that of patients treated with the 8‐week regimen. The adverse events were observed in 29.1% of patients. The main adverse event was pruritus, which was observed in 14.7%. Ten patients (2.0%) discontinued therapy during treatment period. Conclusion: The 12‐week GLE/PIB regimen was well‐tolerated with high virologic efficacy in patients with cirrhosis, experience of DAA, or HCV genotype 3; tolerability and SVR rate were comparable with those of DAA‐naïve, non‐cirrhotic, non‐genotype 3 patients who underwent 8‐week regimen.